Applying Informatics in Tissue Engineering - Xu, Jie; Zhou, Xiaolin; Yang, Daping; Ge, Haiyan; Wang, Qi; Tu, Kang; Guo, Tiefang (Methods of Information in Medicine, 2005)
Objective: To facilitate tissue engineering strategies determination with informatics tools.Methods: Firstly, tissue engineering experimental data were standardized and integrated into a centralized database; secondly, we used data mining tools (e.g. artificial neural networks and decision trees) to predict the outcomes of tissue engineering strategies; thirdly, a strategy design algorithm was developed, and its efficacy was validated with animal experiments; lastly, we constructed an online database and a decision support system for tissue engineering.Results: The artificial neural networks and the decision trees respectively predicted the outcomes of tissue engineering strategies with the predictive accuracy of 95.14% and 85.26%. Following the strategies generated by computer, we cured 18 of the 20 experimental animals with a significantly lower cost than usual.Conclusion: Informatics is beneficial for realizing safe, effective and economical tissue engineering.
Keywords: Tissue engineering; informatics; database; artificial intelligence; machine learning